Gauging Housing Supply in Canada A Stock Approach - Reynaud, Julien (International Monetary Fund, 2015)
This paper estimates Canada's housing stock to gauge the supply-side component of the recent exuberance in the Canadian housing sector. The paper adds to the current related literature by focusing on housing units and reconstructing housing stock and households series. An error correction model is estimated at the provincial level over the period 1980-2013 to estimate a measure of housing stock desequilibrium. The model predicts an excess supply in the order of ½ percent above the housing stock level consistent with fundamentals as of 2013